2009
DOI: 10.1103/physrevb.79.212411
|View full text |Cite
|
Sign up to set email alerts
|

Ni spin switching induced by magnetic frustration in FeMn/Ni/Cu(001)

Abstract: Epitaxially grown FeMn/Ni/Cu(001) films are investigated by Photoemission Electron Microscopy and Magneto-Optic Kerr Effect. We find that as the FeMn overlayer changes from paramagnetic to antiferromagnetic state, it could switch the ferromagnetic Ni spin direction from out-of-plane to in-plane direction of the film. This phenomenon reveals a new mechanism of creating magnetic anisotropy and is attributed to the out-of-plane spin frustration at the FeMn-Ni interface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Different mechanisms have been proposed to explain this phenomenon such as the spin flop coupling [3], local magnetic pinning centers [ 4 ], and the roughness-induced spin compensation [ 5 ], etc. In experiment, it is usually difficult to single out the exact effect of the AFM layer due to the difficulty of a direct measurement of the AFM spin structure and the difficulty of tuning the interfacial spin frustration.…”
Section: Introductionmentioning
confidence: 99%
“…Different mechanisms have been proposed to explain this phenomenon such as the spin flop coupling [3], local magnetic pinning centers [ 4 ], and the roughness-induced spin compensation [ 5 ], etc. In experiment, it is usually difficult to single out the exact effect of the AFM layer due to the difficulty of a direct measurement of the AFM spin structure and the difficulty of tuning the interfacial spin frustration.…”
Section: Introductionmentioning
confidence: 99%
“…It was also shown that a FeMn layer could interact with another FeMn/FM bilayer across a Cu spacer layer [17]. Although the later works on epitaxial FeMn/FM thin films have fruitful results such as the effect of induced Fe moment [18] and the magnetic anisotropies [19,20] However, it is not predictable yet on the easy magnetization axis direction, neither to the effect of foreign atom absorption at the step edges [24]. Thus the different easy axis (the coercivity at room temperature is also plotted in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The former is determined by the magnetic exchange interaction, and the latter is determined by the magnetic anisotropy. We recently showed that the AFM order of FeMn could change the perpendicular anisotropy of a Ni layer in FeMn/Ni/Cu(001) system [8]. To reveal systematically how the AFM layer affect these two properties, we carried out a study on epitaxial FeMn/Ni/Cu(001) system as a function of FeMn and Ni film thicknesses.…”
Section: Introductionmentioning
confidence: 99%